Can Portfolio Rebalancing Explain the Dynamics of Equity Returns, Equity Flows, and Exchange Rates? - Hau, Harald; Rey, Hélène (American Economic Review, 2004)
Can Portfolio Rebalancing Explain the Dynamics of Equity Returns, Equity Flows, and Exchange Rates? by Harald Hau and Hélène Rey. Published in volume 94, issue 2, pages 126-133 of American Economic Review, May 2004